Risk‐taking in the human brain: An activation likelihood estimation meta‐analysis of the balloon analog risk task (BART). Issue 18 (18th August 2022) - Wang, Mengmeng; Zhang, Shunmin; Suo, Tao; Mao, Tianxin; Wang, Fenghua; Deng, Yao; Eickhoff, Simon; Pan, Yu; Jiang, Caihong; Rao, Hengyi
Abstract: The Balloon Analog Risk Task (BART) is increasingly used to assess risk‐taking behavior and brain function. However, the brain networks underlying risk‐taking during the BART and its reliability remain controversial. Here, we combined the activation likelihood estimation (ALE) meta‐analysis with both task‐based and task‐free functional connectivity (FC) analysis to quantitatively synthesize brain networks involved in risk‐taking during the BART, and compared the differences between adults and adolescents studies. Based on 22 pooled publications, the ALE meta‐analysis revealed multiple brain regions in the reward network, salience network, and executive control network underlying risk‐taking during the BART. Compared with adult risk‐taking, adolescent risk‐taking showed greater activation in the insula, putamen, and prefrontal regions. The combination of meta‐analytic connectivity modeling with task‐free FC analysis further confirmed the involvement of the reward, salience, and cognitive control networks in the BART. These findings demonstrate the core brain networks for risk‐taking during the BART and support the utility of the BART for future neuroimaging and developmental research. Abstract : A comprehensive meta‐analysis on neuroimaging studies measured by Balloon Analogue Risk Task (BART) was conducted. Adult and adolescent risk‐taking behaviors measured by BART are rooted in distinct brain regions. The core brain networks for risk‐taking during the BART were explored by combining MACM and RSFC. We present the utility of the BART for future neuroimaging and developmental research.